POTENTIAL LINK PATTERNS OF FISCAL DECENTRALIZATION TO POVERTY REDUCTION IN INDONESIA - Kusumaningrum, Sita Dewi; Sambodo, Deny Purwo (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
Fiscal decentralization is considered to give positive as well as negative impacts for development policy such as povertyÂ reduction. The implementation of fiscal decentralization in Indonesia has changed the patterns of local governmentsâbudget allocation for poverty reduction. Local governments have wider discretion to allocate their budget for povertyÂ reduction strategy. This study aims at observing the potential link patterns of fiscal decentralization to poverty reductionÂ in Indonesian provinces before and in the period of fiscal decentralization implementation. This study applies aÂ descriptive analysis as a method for identifying the potential link patterns of fiscal decentralization to povertyÂ reduction in Indonesia. Firstly, this study identifies the trend of several poverty indicators in Indonesia, namely 1) theÂ percentage rate of poverty; 2) poverty gap index (P1) and poverty severity index (P2); and 3) Human DevelopmentÂ Index (HDI). Secondly, the link of fiscal decentralization to poverty reduction in Indonesia is elaborated using theÂ share of government budget expenditure on relevant sector to total expenditure and the percentage rate of poverty.Â This study shows that there is no clear link pattern of fiscal decentralization to poverty reduction in Indonesia. ThreeÂ link patterns, namely positive link, negative link, and no link appear differently among provinces and regions. SeveralÂ factors that support the conditions need to be elaborated more.